If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -16 = -44 + 9t Reorder the terms: -16 + 5t = -44 + 9t Solving -16 + 5t = -44 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -16 + 5t + -9t = -44 + 9t + -9t Combine like terms: 5t + -9t = -4t -16 + -4t = -44 + 9t + -9t Combine like terms: 9t + -9t = 0 -16 + -4t = -44 + 0 -16 + -4t = -44 Add '16' to each side of the equation. -16 + 16 + -4t = -44 + 16 Combine like terms: -16 + 16 = 0 0 + -4t = -44 + 16 -4t = -44 + 16 Combine like terms: -44 + 16 = -28 -4t = -28 Divide each side by '-4'. t = 7 Simplifying t = 7
| -10+2x=-2 | | 22d/2=14 | | 21x^2+5x-9=0 | | h=-16t^2+96t+880 | | Logs=3.1 | | 5x/4=16 | | 7m+4=24.28 | | (x+10)-(3x+12)=7x+12(11.4) | | z-18/-2=7 | | H=16t^2-16t+60 | | 3(x-2)=2-(x+3)+4 | | k+4=7k-4 | | 2x^2=13-6x | | log3x^2/12 | | 3(x-2)=(x+3)+4 | | 8-5(2x-7)=3x+11 | | 2R-1/5=1-2R/2 | | c^2+7c+16=0 | | 0=4x^2+9x-259 | | n+5=2x | | 18s/5=-11 | | 14-(5x-2)=2(x+8) | | x^5+x+3= | | r-7=29 | | -9+x+10=11 | | 3x=2(50-x)+5 | | 4(m+3)=3(m+4)+m | | 4X^2-3x-18=x^2 | | -5(x+1)-15=11+4 | | 17-(x-4)=-8-9 | | 12b-11-b-9= | | 8x^2+24x-16=0 |